The impact of tax policy on MSME growth in South Jakarta - Maria, Friska Debora (Privietlab, 2025)
This study aims to analyze the impact of tax policy on the growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, focusing on the South Jakarta area. Tax policy, particularly the implementation of the 0.5% Final Income Tax rate based on Government Regulation No. 23 of 2018 and Government Regulation No. 55 of 2022, is an important instrument for encouraging business formalization and increasing MSMEs’ fiscal participation. The approach used is descriptive qualitative, with data collection techniques through in-depth interviews, field observations, and documentation studies of regulations and reports of the Directorate General of Taxes. The results show that tax policy positively impacts MSME growth and sustainability, especially through tariff simplification and increased access to financing facilities. However, the effectiveness of the policy is still influenced by low tax literacy, the complexity of digital administration, and minimal socialization from tax authorities. Some MSMEs still demonstrate instrumental compliance, that is, compliance due to obligation rather than fiscal awareness. Conceptually, this study emphasizes that taxes play a role not only as a fiscal instrument but also as a tool for empowering the people's economy. For MSME tax policies to function optimally, strategies based on fiscal education, administrative digitization, and cross-institutional synergy between the central and regional governments and MSME communities are required.